Ansiedade, classificação radiográfica e controle da dor em exodontias de terceiros molares inferiores - Lisboa, Alessandro Hyczy (2012)
The objective of this study was to compare the existing level of anxiety in patients undergoing different surgical procedures on an outpatient basis, and determine the prevalence of third molar position, establishing its position and inclination, in relation to the classification of Winter and to the classification of Pell & Gregory, and to evaluate the effect of the preemptive use of ibuprofen associated with arginine, etoricoxib and dexamethasone in controlling pain after extraction of mandibular third molar. To evaluate the existence of differences in degree of anxiety in patients undergoing different forms of surgical procedures, the patients were selected (n = 60) who required extractions of third molars, which were compared with others (n = 62) that underwent simple dental extractions. The results indicate that there was no association between anxiety level and gender, but to evaluate the type of surgery used was found that patients undergoing conventional extractions indicated greater levels of anxiety than patients undergoing surgery for third molars. For the radiographic classification, radiographs were analyzed from 1150 third molars which were related to the classification of Winter as its angle to the long axis of the adjacent second molar and Pell & Gregory that determines its position in relation to the branch the mandible and the occlusal plane of the second molar. It was observed that the position was the most common mesioangular (28,52%) as classified by Winter,according to the classification of Gregory & Pell, 27,30% were Class II and 29,82% were in position A. In this randomized clinical trial, parallel and blind study, patients were divided into 4 groups (G): G1 received 600mg of ibuprofen with 555mg of arginine, G2 received 90 mg etoricoxib, G3 who received 8 mg dexamethasone, and G4 received placebo, all administered orally 90 minutes before surgery. Pain intensity was evaluated on a numerical scale of 101 points (101P) and the four point verbal rating scale (VRS) after 2, 4, 6, 8, 12, 24, 36 and 48 hours. Statistical analysis was performed with the Kruskall-Wallis, ANOVA and chi-square test (p 0.05). In the first stage patients were divided into G1 (n = 10), G2 (n = 9), G3 (n = 10) and G4 (n = 13) and it is concluded that all the protocols shown evaluated to be superior to placebo the first 4 hours, and the use of dexamethasone or etoricoxib resulted in lower consumption of rescue analgesia. In the second phase, we selected 60 patients who were randomly divided into 15 for each group. The G4 group had higher pain intensity than the other groups in the 2, 4, 12 and 48 hours. The G3 had more pain than G2 after 2 hours, as well as in relation to G1 after 2 and 4 hours. Again it was observed that all the protocols evaluated proved superior to placebo for both scales and used at different times after surgery, for controlling postoperative pain.